Rare Case of Motor Neuropathy with 5-Fluorouracil Chemotherapy: A Case Report - Shadi S. Alkhayyat, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Peripheral neuropathy is a known side effect of chemotherapy. 5-Fluorouracil is used in treating patients with colon cancer. Literature review reported peripheral neuropathy rarely used with 5-Fluorouracil. All cases described sensory neuropathy and demyelinating nerve injury. A 69-year-old female developed a predominantly motor neuropathy following treatment with 5-Fluorouracil for advanced colorectal cancer. Electrophysiological study indicated axonal injury. Fortunately, the patient recovered her motor functions completely. She declined using further chemotherapy in the future. To date, this is the first reported case of motor peripheral neuropathy with 5-Fluorouracil exposure as no other explanations could be found. In colorectal cancer patients receiving 5-Fluorouracil containing chemotherapy and presenting with motor neuropathy, induced toxicity should be considered if other causes are ruled out.